2018
DOI: 10.1177/0907568218777305
|View full text |Cite
|
Sign up to set email alerts
|

Children and sexting: The case for intergenerational co-learning

Abstract: A note on versions:The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP url' above for details on accessing the published version and note that access may require a subscription.For more information, please contact the WRAP Team at: wrap@warwick.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Young people could be asked what they think about sexual and bodily expression in a broad sense, and then guided to explore how risk and harm emerge from a cultural context characterised by stereotypes and inequalities. There could be a possibility here for what Lee et al (2018) term "inter-generational co-learning" (p. 1) in which adults are positioned less as impartial experts. Instead, the emphasis is on a collaborative approach between adults and young people, in which they come together to rethink social issues and develop solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Young people could be asked what they think about sexual and bodily expression in a broad sense, and then guided to explore how risk and harm emerge from a cultural context characterised by stereotypes and inequalities. There could be a possibility here for what Lee et al (2018) term "inter-generational co-learning" (p. 1) in which adults are positioned less as impartial experts. Instead, the emphasis is on a collaborative approach between adults and young people, in which they come together to rethink social issues and develop solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, while children are important owners of knowledge and providers of peer support, they are not decision makers. Co-learning (Lee et al, 2018) or co-production of services (Tisdall, 2017) together with children is not something the professionals explicitly reported as an aim, as this would also require them to view children as decision makers.…”
Section: Discussionmentioning
confidence: 99%
“…As stated by a few of the professionals in this study, collective user participation is a future challenge and could help professionals tackle ethical challenges such as child anonymity and the long-lasting risks associated with publicity. However, this needs a strong commitment to co-development: collective structures should not be developed for but together with children (Kiili and Larkins, 2018;Lee et al, 2018;Tisdall, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Participants preferred parents to approach a teacher who could then help by speaking to the boyfriend and his parents. The importance of having a shared understanding of sexting is discussed by Lee et al (2018) in the context of intergenerational co-learning to provide opportunities for children to articulate and reflect on how they negotiate sexual intimacy and for adults to respond creatively.…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known of the views of young people who have engaged in sexting, and their experiences of involvement with professionals, including law enforcement and child protection agencies (García-Gómez, 2017). Lee et al (2018) have called for creative responses to sexting which draws on adults' and children's understandings and views. Jørgensen, Weckesser, Turner and Wade ( 2019) explored young people's views on sexting education and concluded that we need to give more attention to young people's voices and acknowledge children as experts in their own lives.…”
Section: Rational For This Studymentioning
confidence: 99%